Characterization, formulation and evaluation of glibenclamide with ß-cyclodextrin inclusion complexes tablets - Yandi Syukri; Farida Ulfa; Asih Lestari; Lelita Ayu Saputri; Rochmy Istikharah; Aris Perdana Kusuma (JKKI : Jurnal Kedokteran dan Kesehatan Indonesia, 2018)
Background: Glibenclamide is an oral antidiabetic drug which is practically insoluble in water. Formation of ß-cyclodextrin inclusion complex was able to increase glibenclamide solubility. Objective: Aims of this study are to characterize, formulate and evaluate  inclusion complex tablets of glibenclamide to meet the requirements in Pharmacopeia.Methods: Inclusion complex was prepared in a 1: 1 and 1: 2 molar ratio  by spray drying method. Characterization were performed by using Fourier Transform Infrared (FTIR) spectroscopy and Scanning Electron Microscope (SEM). Further, it was formulated into tablets by direct compression technique using primojel and crospovidone as disintegrants.   Uniformity weight, hardness, friability, disintegration, and tablets were evaluated include dissolution. Dissolution studies of inclusion complex were performed by using United States Pharmacopeia (USP) II apparatus.  Drug concentration dissolution was determined with high pressure liquid chromatography (HPLC).Results: Result of FTIR and SEM provided evidence of  glibenclamide and ß-cyclodextrin complex formation after using spray drying methods. The tablet evaluation with primojel and crospovidone as disintegrant showed that increase concentration of disintegrant would increase disintegration time of the tablets. All of the formulas meet the requirements in the Pharmacopoeia.Conclusion: The inclusion complex of glibenclamide–ß cyclodextrin successfully used for enhancing the solubility of glibenclamide. The tablets meet the requirements in Pharmacopeia.